Experimental Model of Pulmonary Thrombosis in Rat - Tomikawa, Munehiro; Ogawa, Hidemasa; Abiko, Yasushi (Thrombosis and Haemostasis, 1974)
Experimental pulmonary thrombosis was induced in rats by intravenous infusion of 0.7 M lactic acid at a rate of 1.4 ml/100 g/hr for 2 hr. As acidosis progressed, a hyper-coagulable state developed and microthrombi were formed predominantly in the lung, but not conspicuously in other organs. Pulmonary thrombi thus formed were composed of aggregated platelets in the initial stage, and of fibrin in later stages. They progressively dissolved and had completely disappeared 12 hr after cessation of the lactic acid infusion.During the infusion of lactic acid, the following changes were observed: progressive decreases in platelet count, fibrinogen, antiplasmin activity and fibrinolytic activity, and progressive increase in platelet adhesiveness. Plasma clotting time decreased to its shortest interval after one hour of the lactic acid infusion and remained at that level during the rest of the infusion. No fibrin degradation products (FDP) were detected.After cessation of the lactic acid infusion, these parameters, except for fibrinolytic activity, tended to return to normal gradually while FDP increased markedly. Fibrinolytic activity measured by eugolobulin lysis time remained low, suggesting depletion of vascular activator. Plasminogen level began to fall gradually 6 hr after cessation of the lactic acid infusion.These dynamic coagulo-fibrinolytic changes are discussed in relation to the morphological changes of thrombi.